Improving Students Ability To Identify Main Ideas Through Guided Reading Strategy Grade VIII - Sinambela, Joyada; Selviana Napitupulu (CV PUTRA PUBLISHER, 2025)
Reading comprehension is a fundamental skill in learning English, as it enables students to understand written texts effectively and construct meaning from what they read. One of the main viralslot problems faced by junior high school students is difficulty in identifying the main idea of a text, which often results in poor overall comprehension. This difficulty is commonly caused by students’ limited reading strategies and lack of guided support during the reading process. Therefore, an effective instructional strategy is needed to help students improve their reading comprehension skills. This study aimed to improve students’ ability to identify main ideas through the implementation of the Guided Reading strategy at Grade VIII of SMP Swasta Teladan. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. The participants of this study were 30 eighth-grade students. Data were collected using reading comprehension tests, observation sheets, and field notes. The results of the study showed a significant improvement in students’ reading comprehension after the implementation of the Guided Reading strategy. The mean score increased from 61.2 in the pre-test to 82.0 in the post-test of Cycle II. Furthermore, the percentage of students who achieved the minimum mastery criterion (70) increased substantially from 13% in the pre-test to 93% in the final test. Observation results also indicated that students became more active, motivated, and confident during reading activities. In conclusion, the Guided Reading strategy was effective in improving students’ ability to identify main ideas and enhancing their overall reading comprehension. This study implies that Guided Reading can be an effective strategy for supporting students’ reading development in junior high school.